Korelasi antara Kemampuan Imajinasi dengan Keterampilan Menulis Teks Deskriptif Siswa Kelas VII MTS Al Hidayah Sukatani - Dinda Fakhira (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the correlation between students’ imagination ability and their descriptive writing skills among seventh-grade students at MTs Al Hidayah Sukatani. Writing skills are a crucial component of Indonesian language learning, especially in producing descriptive texts that require students to portray objects, scenes, or events in a detailed and engaging manner. In this process, imagination plays an essential role in forming mental imagery, creating original content, and organizing ideas creatively. This research employed a quantitative approach with a correlational method. The sample consisted of 34 students selected from the total population using the Slovin formula. Data collection was carried out through a closed-ended questionnaire to measure imagination ability, based on Torrance’s theory, and a descriptive writing test assessed using five criteria adapted from Nurgiyantoro: idea content, content organization, grammar, vocabulary and structure, and spelling. Instrument validity and reliability were tested before the main data collection. The data were analyzed using Pearson correlation with the help of SPSS version 25. The results showed a significant positive correlation between students’ imagination and their descriptive writing skills. This indicates that the higher the students’ imagination, the better the quality of their descriptive writing. These findings highlight the importance of imagination in the writing process and the need for Indonesian language teachers to provide opportunities for students to explore and express their creative ideas. Thus, imagination is not only a tool for writing but also a key element in enhancing the overall quality of language learning